(untitled) (e-Journal of Linguistics, 2023)
The paper presents the results of research aimed at the acoustic and perceptual analysis of onset and coda clusters from standard Slovak that violate the principle of sonority. The research is based on Engstrand and Ericsdotter’s (1999) claim that clusters violating sonority are perceptually advantageous over those that follow the sonority principle. The analysis was carried out on a sample of test nonsense words with the initial combinations /sp, st, sk/ and final combinations /ps, ts, ks/. The data were produced and evaluated by native Slovak language speakers. The results of the research support the assumption about the perceptual advantage of clusters that are not in accordance with sonority.